2018
DOI: 10.1007/s12975-018-0640-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Barometric Pressure and Temperature on Acute Ischemic Stroke Hospitalization in Augusta, GA

Abstract: Several studies worldwide have demonstrated significant relationships between meteorological parameters and stroke events. However, authors often reported discordant effects of both barometric pressure and air temperature on stroke occurrence. The present study investigated whether there was an association between weather parameters (barometric pressure and temperature) and ischemic stroke hospitalization. The aim of the study was to find out whether daily barometric pressure may be used as a prognostic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
12
1
1
Order By: Relevance
“…Daily numbers of ischemic stroke onset were modeled using generalized linear Poisson regression models to study the association between stroke onset and meteorological variables including air temperature (mean, maximum, minimum, diurnal variation), barometric pressure (mean, maximum, minimum, diurnal variation), and relative humidity. 6,9,14 Each meteorological variable was modeled separately after adjusting for day of week, public holiday (binary variable) and AQI, removing the confounding effect of those factors on stroke onset. Modeling was also repeated in the subgroup analysis (<75 years vs. ≥75years; male vs. female).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily numbers of ischemic stroke onset were modeled using generalized linear Poisson regression models to study the association between stroke onset and meteorological variables including air temperature (mean, maximum, minimum, diurnal variation), barometric pressure (mean, maximum, minimum, diurnal variation), and relative humidity. 6,9,14 Each meteorological variable was modeled separately after adjusting for day of week, public holiday (binary variable) and AQI, removing the confounding effect of those factors on stroke onset. Modeling was also repeated in the subgroup analysis (<75 years vs. ≥75years; male vs. female).…”
Section: Discussionmentioning
confidence: 99%
“…Both immediate and delayed effects of weather conditions on stroke occurrence were revealed. [6][7][8][9] However, existing studies often reported discordant effects of these meteorological parameters on ischemic stroke occurrence. For example, conclusions on the temperature and barometric pressure were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the negative influence of changes of atmospheric pressure on human health has been established. Significant correlations were discovered between daily barometric pressure variation and daily stroke hospitalization [4], between low barometric pressure and aggressive behavior in patients in psychiatric hospitals [5], between low barometric pressure and increased pain and stress levels in the patients with fibromyalgia [6]. Thus, changes in atmospheric pressure as an aspect of global warming could have a serious effect on public health.…”
Section: Introductionmentioning
confidence: 99%
“…Several diseases have been reported to be related to barometric pressure, including acute ischemic stroke [8], benign paroxysmal positional vertigo [9], and migraine headache [10]. According to Boyle's law, it is assumed that the decreased barometric pressure would cause the volume of intestinal gas to expand.…”
mentioning
confidence: 99%